Dear brother : letters of William Clark to Jonathan Clark - Clark, William, 1770-1838 (Yale Western Americana series., 2002)
Over the course of his career, American explorer William Clark (1770-1838) wrote at least forty-five letters to his older brother Jonathan, including six that were written during the epic Lewis and Clark Expedition. This book publishes many of these letters for the first time, revealing important details about the expedition, the mysterious death of Meriwether Lewis, the status of Clark's slave York (the first African American known to have crossed the continent from coast to coast), and other matters of historical significance. There are letters concerning the establishment of the Corps of Discovery's first winter camp in December 1803, preparations for setting out into the country west of Fort Mandan in 1805, and Clark's 1807 fossil dig at Big Bone Lick, Kentucky. There are also letters about Lewis's disturbed final days that shed light on whether he committed suicide or was murdered. Still other letters chronicle the fate of York after the expedition; we learn the details of Clark and York's falling out and subsequent alienation. Together the letters and the introductions and annotations by James J. Holmberg provide valuable insights into the lives of Lewis and Clark and the world of Jeffersonian America.